Evaluating the Professional Efficiency of Primary School Teachers in Teaching Rafidain English Course for Iraq, Book I (Journal Of Educational and Psychological Researches, 2007)
Teaching techniques are the vehicles, which are used by teachers to help pupils learn and gain experiences and create positive classroom activities, as much as these techniques are varied, they lead to successful and fruitful learning in the foreign language. They help teachers achieve their objectives (Asowrth, 1985: 124).    The English language teacher's work is an active and purposeful one when he can plan carefully and frequently make the necessary changes in the contents and methods of teaching programme to fit the interest and needs of pupils. It seems that the majority of primary English teachers' interests does not go far in planning their work, and do not understand which of the methods could result for the benefit of the pupils, yet a good English language teacher could make a success of any method (Ramadan, 1998: 2).    However, the significance of this problem lies in the fact that it tackles the process of using techniques of teaching Book 1 at the primary schools, which are considered one of the main factors in teaching EFL, i.e., the significance of the problem lies in identifying the actual techniques used in teaching Book 1 and then assessing the extent of using the officially recommended techniques. The researchers will modify the followed techniques and come up with some practical suggestions and recommendations.    This study attempts to explore the exact teaching techniques used by teachers in teaching Book 1, in order to find out whether there is a gap between what is supposed to be followed by teachers and what is actually followed in teaching Book 1 of RECI in the light of the modern trends of teaching English as a foreign language.